Co-morbid risk factors and NSAID use among white and black Americans that predicts overall survival from diagnosed colon cancer. - Minoru Koi; Yoshiki Okita; Koki Takeda; Erika S Koeppe; Elena M Stoffel; Joseph A Galanko; Amber N McCoy; Temitope Keku; John M Carethers (PLoS ONE, 2020)
Black Americans (BA) have higher incidence and higher mortality rates for colorectal cancers (CRC) as compared to White Americans (WA). While there are several identified risk factors associated with the development of CRC and evidence that high levels of adequate screening can reduce differences in incidence for CRC between BA and WA, there remains little data regarding patient co-morbid contributions towards survival once an individual has CRC. Here we set out to identify patient risk factors that influenced overall survival in a cohort of 293 BA and 348 WA with colon cancer. Amid our cohort, we found that patients' age, tobacco usage, and pre-diagnosed medical conditions such as hypertension and diabetes were associated with shorter overall survival (OS) from colon cancer. We identified pre-diagnosed hypertension and diabetes among BA were responsible for one-third of the colon cancer mortality disparity compared with WA. We also identified long-term regular use of non-steroidal anti-inflammatory drugs (NSAIDs), including aspirin, was associated with shorter OS from colon cancer among WA >65 years of age, but not younger WA patients or any aged BA patients. Our results raise the importance of not only treating the colon cancer itself, but also taking into consideration co-morbid medical conditions and NSAID usage to enhance patient OS. Further evaluation regarding adequate treatment of co-morbidities and timing of NSAID continuance after cancer therapy will need to be studied.